Hardscrabble road - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2006)
When a local Philadelphia radio host known for his incendiary right-wing tirades is arrested for illegal possession of prescription drugs, the incident sets into motion a series of events that leads ultimately to the death of a homeless man. In the complicated mix are the local Benedictine monastery, a Nobel Prize-winning leftist academic, and a homeless advocacy group, among others.Gregor Demarkian, a retired FBI agent, is hired by a local legal project to look into the circumstances surrounding the death of their former client-a task that leads Demarkian through a mirror-maze of motives and actors as he struggles to unravel a most complex puzzle before the killer strikes again.